Economic Dislocation and Contract Renegotiation in New Zealand and Japan: A Preliminary Empirical Study - Nottage, L (Victoria University of Wellington Law Review, 1997)
This article reports on results so far from ongoing empirical research into attitudes and practices in New Zealand and Japan as to contract renegotiation in cases of extreme economic dislocation. It reports primarily on a survey administered to students in both countries. It adds some preliminary results from a more ambitious survey and follow-up interviews with companies; final results will follow in early 1997. In the interim, the article draws some possible implications for reform of the law of frustration of contract, and for legal theory more generally.